DNA-mediated self-assembly oxidative damage amplifier combined with copper and MTH1 inhibitor for cancer therapy - Cui Ren; Zhiyong Shi; Xiaowen Zhang; Xueer Yu; Yang Gao; Zhi Qi; Yu Chen; Yong Wang (Bioactive Materials)
Chemo-dynamic therapy (CDT) has a great potential in tumor extirpation. It entails producing hypertoxic reactive oxygen species (ROS) that damage the DNA of tumor cells and other biomacromolecules. However, the efficiency of CDT is severely hampered by the massive presence of glutathione (GSH) in tumor cells and the interference of ROS defense systems, such as Mutt homolog 1 (MTH1) protein sanitizes ROS-oxidized nucleotide pools. In this research, DNA-mediated self-assembly nanoparticles (HTCG@TA NPs) were engineered with high-performance amplified oxidative damage and gene therapy effect for synergistic anti-tumor treatment. Cu2+ was converted into Cu + by redox reactions to deplete GSH while H2O2 was catalyzed to generate hydroxyl radicals (·OH). As a result, the ROS level was evidently improved. Moreover, controllable-released TH588 prevented MTH1-mediated DNA repairing, thus aggravated oxidative damage to tumor cells. Meanwhile, the released functional nucleic acid G3139 downregulated the expression of Bcl-2, and accelerated the apoptosis of tumor cells. In conclusion, the HTCG@TA demonstrated significant effect in oxidative damage amplification and tumor inhibition both in vitro and in vivo, which has provided a new outlook for the clinical application of chemo-dynamic tumor treatment and synergistic gene therapy with self-delivery nanoplatforms.